GST And the Influencing Factors of Prices Hikes In Daily and Consumable Goods after the Implementation of GST (Journal of Science, Technology and Innovation Policy, 2021)
As an economic instrument, tax is very important for a country in collecting or earning revenue for national and economic development. The multiple weaknesses of Sales and Trade Taxes (SST) like a double tax on consumers, no tax relief on exported goods, price transfer issues, high flow of capital value out of Malaysia and inability of government to record every commercial transaction details in the national accounts have convinced the government to introduce a new taxation system namely Goods and Services Tax (GST). GST is also seen as a solution to the shortage of government funds. However, long before GST was introduced in April 2015 and till to date, the public has non-stop complaining about the possibility of price hikes in goods and services. Literature reviews on the experiences of countries in implementing GST together with pre-GST simulation in Malaysia highlight positively the effect of GST on Consumer Price Index and reduction of prices. Despite the assurance and various efforts of the government in keeping the prices of goods remain the same after GST the prices continue to increase. Report by the Department of Statistics, Malaysia showed that the price increases in Malaysia has occurred every year before and after the implementation of the GST. This paper is interested to know if GST is the sole and the real cause of price hikes or there are other causes and if so, what are those causes. The findings of this paper indicated that GST is one of the factors in price hikes but is not the only one responsible for and causing the rise in prices of goods in Malaysia. In fact, there are other elements that are equally responsible for increasing the price of goods and services in Malaysia.
Keywords: GST; Price hikes; Consumer Price Index